Ancaman Produk Pengganti Dan Perkembangan Teknologi: Analisis Kritis Dalam Kerangka Porter’s Five Forces - Debbie Masitha; Winanti, Lilik; Nofriadi, Dedi; Husna, Asmaul (Program Studi Manajemen FEBM UMRAH, 2026)
The threat of substitutes and technological change represent critical factors in shaping competitive dynamics within the Porter’s Five Forces framework. This study aims to analyze the impact of technological development and substitute product innovation on industry competition and firms’ competitive advantage in modern industries. The research employs a literature review and empirical analysis of relevant previous studies. The findings indicate that substitution threats no longer arise solely from similar products but increasingly from technological advancements that introduce more efficient and cost-effective alternative solutions. Firms that fail to adapt to technological change and innovation are likely to experience a significant erosion of competitive advantage. Therefore, this study emphasizes the importance of strategic research and development (R&D), continuous innovation, and digital transformation as essential strategies for addressing the threat of substitutes